Variation in students' conceptions of classroom management - Correia, Ana (Proceedings of the International Symposium on Education and Psychology, 2017)
ISSN: 2226-6275

Using digital reading platforms to develop Chinese elementary students' English reading - Correia, Ana; Norte, Patrícia; Garrot, João (Proceedings of the International Symposium on Education and Psychology, 2017)
ISSN: 2226-6275

Sounding Architecture: Inter-Disciplinary Studio at HKU - Barbosa, Alvaro; Tsang, Thomas (Proceedings of the International Conference on New Interfaces for Musical Expression, 2017)
Sounding Architecture, is the first collaborative teaching development between Department of Architecture and Department of Music at the University of Hong Kong (HKU), introduced in Fall 2016. In this paper we present critical observations about the studio after a final public presentation of all projects. The Review was conducted with demonstrations by groups of students supervised by different Lecturer, in each case focusing on a different strategy to create a connection between Sound, Music, Acoustics, Space and Architectural Design. There was an assumption that the core working process would have to include the design of a new musical instrument, which in some cases became the final deliverable of the Studio and in other cases a step in a process that leads to a different outcome (such as an architectural Design, a performance or social experiment). One other relevant aspect was that Digital technology was used in the design and fabrication of the physical instruments' prototypes, but in very few cases, it was used in the actual generation or enhancement of sound, with the instruments relying almost exclusively in acoustic and mechanical sound.
GSCC: 0000000

New geochemical constraints on I-type granites of Macao: evidences for fractional crystallization and petrogenetic affinities with Jurassic-Cretaceous granites in SE China - Dias, Ágata; Quelhas, P; Mata, J; Lou, U T; Borges, R; Ribeiro, M. L (2017)

Creative Engagement: Multimodal digital games in children's learning environment in Macau S.A.R. - Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts, 2017)
One of the biggest challenges that we have encountered, when trying to encourage digital games in schools, is trying to explain what its benefits are in teaching and learning environments. In this pilot experimental study we explore how multimodal audio and visual games can be used in learning environments for children, specifically by fostering creative behaviors through User-Centered design approaches. To achieve this objective, a framework is being developed with multimodal experiences based on flexible design patterns that exploits basic visual and audio elements, allowing children from three to six years of age to play and learn through fun and subsequently trigger creative behaviors. These studies are making use of tangible objects, digital games and mobile platforms. We are making use of commercial digital games to understand and discuss the affordances of these games in an educational environment and how they support creativity in learning. (Fig.1)
Keywords: Children; Creative Learning; Devices; Digital Games; Mobile; Multimodal; Tangible Technologies; User-Centered Design

Computer Literacy Teaching Using Peer Learning and Under the Confucian Heritage Cultural Settings of Macao, China - Wong, Kelvin; Neves, Ana; Negreiros, João (International Conference Educational Technologies, 2017, 2017)
University students in Macao are required to attend computer literacy courses to raise their basic skills levels and knowledge as part of their literacy foundation. Still, teachers frequently complain about the weak IT skills of many students, suggesting that most of them may not be benefiting sufficiently from their computer literacy courses. This research proposes an enhanced framework based on constructivist principles by using peer-tutoring to increase cost effectiveness and to improve student outcomes. Essential to this proposed model is the training of former course graduates as peer-instructors to achieve high quality learning results. At Instituto de Formação Turistica (IFT), a case study was used to evaluate its effectiveness using a qualitative analysis. In Macao, most students have a Confucian Heritage Cultural (CHC) background and the current findings demonstrate that students share more easily their learning difficulties within their group as their interpersonal relationships improve. It is suggested that since CHC cooperative learning is primarily based on bonds, students involved in this 'relationship-first, learning-second' type shared a larger amount of knowledge and social skills, a dual positive outcome. Moreover, English language is a major barrier for the understanding of the teacher’s message to Chinese students. Meanwhile, the negative Western concept of plagiarism is replaced, under the CHC, as the ‘face giving’ and it is directly based on the relationship intensity to 'help friends'. At last, peer-tutors play a key role in the student increase internal motivation regarding the joy of the learning process.

Audience Participation in Interactive Art Systems: Is Instructional Signage a Necessary Evil? - Cordeiro, João; Martins de Abreu, F.; Estadieu, Gerald (Proceedings of the 8th International Conference on Digital Arts, 2017)
2 citations (Crossref) [2022-10-27]

3D Printing Objects As Installation Art: Standing Humanity: 3D Yan Character - Estadieu, Gérald; Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts (ARTECH 217), 2017)
0 citations (Crossref) [2022-09-21] GSCC: 0000000